2000
DOI: 10.1046/j.1365-2648.2000.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence: quality of life before and after coronary artery bypass surgery — a longitudinal study

Abstract: The attention to patient outcome has nowadays extended from morbidity and mortality to an aspect of patients' benefits in terms of quality of life. One factor crucial for quality of life is coping capacity, in this study represented by the sense of coherence concept. Physical status and emotional state (often measured by comprehensive instruments not always suitable for clinical use) are also additionally used to reflect quality of life. The purpose was therefore to study sense of coherence and emotional state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 43 publications
10
103
3
1
Order By: Relevance
“…Importantly, the better sense of coherence in Sudanese diabetic subjects with LLA was linked to worse functional and mobility status per se, as it correlated negatively to both physical functioning and role physical indicating remarkable failure in coping capacity in relation to amputation (Karlsson et al 2000). Gender differences were not observed grouping this study, however, women were shown to score relatively low on SOC due to exclusive social factors in the community rather than biological differences (Erikson and Lindström 2005).…”
Section: Discussioncontrasting
confidence: 39%
“…Importantly, the better sense of coherence in Sudanese diabetic subjects with LLA was linked to worse functional and mobility status per se, as it correlated negatively to both physical functioning and role physical indicating remarkable failure in coping capacity in relation to amputation (Karlsson et al 2000). Gender differences were not observed grouping this study, however, women were shown to score relatively low on SOC due to exclusive social factors in the community rather than biological differences (Erikson and Lindström 2005).…”
Section: Discussioncontrasting
confidence: 39%
“…Sharing "common" experiences can ease efforts to cope with the experienced drama, and initiate as well as keep up day-to-day activities involving lifestyle changes and secondary prevention recommendations. Although previous studies report that measures of 'sense of coherence' as stable post CABG (24), findings from this study highlight that health providers should be aware of individuals' needs expressed as challenges to maintain role expectations, and uncertainty or existential questions to support male and female CABG convalescents' 'sense of coherence' (5).…”
Section: Discussionmentioning
confidence: 81%
“…It is a global orientation to view life as structured, manageable and meaningful. Independent of the measure used, a stronger SOC has been shown to be associated with better HRQoL in persons who have undergone coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) [17,18], cardiac arrest survivors [19] and angina patients [20]. Furthermore, a positive association between high SOC and good HRQoL has been found among patients with lower-limb ischaemia [21], patients hospitalised with a cardiac condition [22], CHD patients [23] and in men as well as older women following myocardial infarction [24,25].…”
Section: Introductionmentioning
confidence: 99%